Automated virtual reality (VR) cognitive therapy for patients with psychosis: study protocol for a single-blind parallel group randomised controlled trial (gameChange). Issue 8 (27th August 2019) - Freeman, Daniel; Yu, Ly-Mee; Kabir, Thomas; Martin, Jen; Craven, Michael; Leal, José; Lambe, Sinéad; Brown, Susan; Morrison, Anthony; Chapman, Kate; Dudley, Robert; O'Regan, Eileen; et al.
Abstract : Introduction: Many patients with psychosis experience everyday social situations as anxiety-provoking. The fears can arise, for example, from paranoia, hallucinations, social anxiety or negative-self beliefs. The fears lead patients to withdraw from activities, and this isolation leads to a cycle of worsening physical and mental health. Breaking this cycle requires highly active treatment directly in the troubling situations so that patients learn that they can safely and confidently enter them. However patients with psychosis seldom receive such life-changing interventions. To solve this problem we have developed an automated psychological treatment delivered in virtual reality (VR). It allows patients to experience computer simulations of the situations that they find anxiety-provoking. A virtual coach guides patients, using cognitive techniques, in how to overcome their fears. Patients are willing to enter VR simulations of anxiety-provoking situations because they know the simulations are not real, but the learning made transfers to the real world. Methods and analysis: 432 patients with psychosis and anxious avoidance of social situations will be recruited from National Health Service (NHS) secondary care services. In the gameChange trial, they will be randomised (1:1) to the six-session VR cognitive treatment added to treatment as usual or treatment as usual alone. Assessments will be conducted at 0, 6 (post-treatment) and 26 weeks by a researcher blind to allocation. The primary outcome is avoidance and distress in real-life situations, using a behavioural assessment task, at 6 weeks. The secondary outcomes are psychiatric symptoms, activity levels and quality of life. All main analyses will be intention-to-treat. Moderation and mediation will be tested. An economic evaluation will be conducted. Ethics and dissemination: The trial has received ethical approval from the NHS South Central - Oxford B Research Ethics Committee (19/SC/0075). A key output will be a high-quality automated VR treatment for patients to overcome anxious avoidance of social situations. Trial registration number: ISRCTN17308399 .